Disease and fertility: Evidence from the 1918 influenza pandemic in Sweden - Nina Boberg-Fazlić; Maryna Ivets; Martin Karlsson; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2017)
This paper studies the effect of the 1918-19 influenza pandemic on fertility using a historical dataset from Sweden. Our results suggest an immediate reduction in fertility driven by morbidity, and additional behavioral effects driven by mortality. We find some evidence of community rebuilding and replacement fertility, but the net long-term effect is fertility reduction. In districts highly affected by the flu there is also an improvement in parental quality: we observe a relative increase in births to married women and better-off city dwellers. Our findings help understand the link between mortality and fertility, one of the central relations in demography, and show that several factors - including disruptions to marriage and labor markets - contribute to fertility reduction in the long term. Our results are consistent with studies that find a positive fertility response following natural disasters, but with high-quality historical data we show that this effect is short-lived.
Keywords: I12; J11; J13; 330; 1918-19 influenza pandemic; Influenza and pneumonia mortality; Fertility; Difference-in-Differences